2001
DOI: 10.1006/icar.2000.6521
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Domino: The Dark Side of Iapetus

Abstract: We present new spectra of the leading and trailing hemispheres of lapetus from 2.4 to 3.8 p.m. We have combined the leading hemisphere spectra with previous observations by others to construct a composite spectrmn of the dark side (leading) hemisphere from 0.3 to 3.8 p.m. We review attempts to deduce the composition of the dark material from previously avai|able spectrophotometry. None of them (numbering more than 20 million!)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 55 publications
0
82
0
Order By: Relevance
“…The CGS4 data were obtained in individual spectral segments of 0.15-0.64 µm that were also separated in time, while the SpeX data were obtained simultaneously over the region 0.8-2.5 µm in several orders of a cross-dispersed echelle. Our study of the low-albedo hemisphere of Iapetus has been reported by Owen et al (2001), and our Phoebe study appears in Owen et al (1999). In this paper, we present additional results from this program.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The CGS4 data were obtained in individual spectral segments of 0.15-0.64 µm that were also separated in time, while the SpeX data were obtained simultaneously over the region 0.8-2.5 µm in several orders of a cross-dispersed echelle. Our study of the low-albedo hemisphere of Iapetus has been reported by Owen et al (2001), and our Phoebe study appears in Owen et al (1999). In this paper, we present additional results from this program.…”
Section: Introductionmentioning
confidence: 66%
“…Tholins are strongly colored, and mostly affect the short wavelength portion (0.3-1.4 µm) of the spectrum, where H 2 O ice is nearly neutral in reflectance. Certain tholins have a strong N-H absorption band at 3 µm, which appears in the model spectra (note particularly the models of Iapetus in Owen et al, 2001).…”
Section: Rheamentioning
confidence: 98%
“…Surfaces made up of organics exposed to high amounts of radiation (e.g., inner solar system, or older surfaces in the outer solar system) get darker and blacker (or grayer), whereas organic-containing surfaces exposed to less radiation are redder (Andronico et al 1987). This explanation has been used, for instance, to explain the (visible) gray color of Phoebe compared to the red color of the dark material on Iapetus (Strazzulla 1986; Thompson et al 1987;Allamandola et al 1988;Owen et al 2001) as well as the gray color of KBOs of large eccentricity with aphelions >70 AU compared to visibly redder, cold outer solar system KBOs (perihelion >40 AU; Tegler et al 2003). We postulate here that the corresponding trend in the UV is toward older, more weathered regions on Callisto becoming darker and the 350 nm absorption band strength decreasing, which tends to give the spectrum an overall redder slope in the UV.…”
Section: Discussionmentioning
confidence: 99%
“…Whether observed absorption bands in Centaur and KBO spectra (see, e.g., Brown 2000, Bauer et al 2002, and Barucci et al 2002 are caused by species that are intimately mixed or spatially variegated may not only significantly change the compositional fits to the spec-Vol. 610 tra but may also provide clues as to whether these species are exposed or implanted by exogenic or endogenic processes (Hainaut et al 2000;Owen et al 2001). Color and albedo correlations have broader implications regarding the reported color bimodality or gradients among outer solar system small bodies (e.g., Tegler & Romanishin 2003;Bauer et al 2003) and how to interpret these observed phenomena.…”
Section: Discussionmentioning
confidence: 99%